Carbon-based amendments for sustainable remediation of arsenic-contaminated paddy soils: An insight to greenhouse gases - Muhammad Mahroz Hussain; Muhammad Junaid Nazir; Qasim ali; Nabeel Khan Niazi; Hamna Bashir; Shengsen Wang; Jörg Rinklebe; Ghulam Abbas; Sarmad Frogh Arshad; Muhammad Anwar (Ecotoxicology and Environmental Safety)
Soil organic carbon (SOC) affects biogeochemistry of arsenic (As) in soil, however, response of As bioavailability in different-textured soils to SOC sources remained partially explored. Therefore, two texturally different natural As-contaminated soils were used to unveil immobilization of As, soil biochemical health and carbon dynamics in soil fractions using different carbon-based organic amendments (biogas slurry (BGS), cow dung (CD), farmyard manure (FYM), biochar (BC), commercial coal, sugarcane bagasse (SCB) and lignite (LIG)). Results showed a significant reduction in As concentration by 25–89 % in the sandy loam soil and 24–78 % in the clay loam soil maximum with CD and BC application. Curve fit regression model elucidated that minimum residual As pool was found with CD i.e., 182 and 167 mg As kg−1 in contrasting texture soils. Nitrous oxide and methane emissions was also significantly (p < 0.05) enhanced by 3-folds in both textural soils. A significant increase in soil microbial biomass carbon (MBC) and dissolved organic carbon (DOC) was observed in the sandy loam soil (2-fold higher) and by 7-fold in the clay loam soil with CD, BC and FYM. Soil extracellular enzymes activity significantly (p < 0.05) increased with CD and BC; except acid phosphatase. The application of CD and BC effectively reduces As mobilization, likely by forming stable organo-As complexes, while also improving soil biochemical health and extracellular enzyme activities.